SUPPORTING PUBLIC UNDERSTANDING IN HANDLING COVID 19 AND PUBLIC EDUCATION IN THE NEW NORMAL ERA - Annuril, Kheli Fitria; Mardiani, Mardiani; Riyadi, Agung; Hariadi, Efrizon (Khidmatul Ummah: Jurnal Pengabdian Kepada Masyarakat, 2024)
Efforts are made to provide support in exploring the potential of the community so that they are empowered and able to participate in preventing the transmission of COVID-19. The method of activity is socialization, health services, checking blood sugar levels, health counseling, fostering active cadres and empowering families which are carried out in synergy with the Benteng District Health Office and puskesmas. The implementation of activities allocated for 6 months in Lubuk Sini Village. Community empowerment activities in Covid-19 prevention at the village level involve various elements in the community, such as; Village heads and officials, health cadres, puskesmas officers and the community in the area. All elements of society have roles and functions in accordance with the conditions that occur in their respective regions. With community empowerment in preventing COVID-19 at the village level, this is done so that everyone is able to identify and recognize risks that can support the implementation of Covid-19 prevention activities in their area and apply a clean lifestyle in the era of the Covid-19 pandemic. The results of socialization and training can increase the knowledge, attitudes and behavior of Village cadres to convey back to the community more broadly about Covid 19. Continuous monitoring and evaluation of cadres needs to be carried out so that cadres play an active role in improving the health of villagers, especially in preventing Covid 19.